Experimental periodontal disease treatment by subgingigval irrigation with tetracycline hidrochloride in rats - Fernandes, Leandro Araújo [UNESP]; Martins, Tiago Marchi [UNESP]; Almeida, Juliano Milanezi de [UNESP]; Nagata, Maria José Hitomi [UNESP]; Theodoro, Letícia Helena [UNESP]; Garcia, Valdir Gouveia [UNESP]; Bosco, Alvaro Freancisco [UNESP] (FapUNIFESP (SciELO), 2010)
Objective: The aim of this study was to compare subgingival irrigation with tetracycline hydrochloride (TTC-HCL) as adjunctive treatment to scaling and root planning (SRP) on induced periodontitis in rats. Material and Methods: In 60 rats, periodontal disease was ligature-induced at the mandibular left first molar. After 7 days, the ligature was removed and all animals were submitted to SRP, and divided into 2 groups according to the following treatment: C (n=30) – subgingival irrigation with 1 mL of saline; T (n=30) – subgingival irrigation with 1 mL of TTC-HCL (50 mg/mL). Ten animals in each group were euthanized at 7, 15 and 30 days posttreatment. The histometric values were statistically analyzed (p<0.05). Results: In the histometric analysis, at 7, 15 and 30 days, Group T (0.72±0.05 mm2, 0.57±0.14 mm2, 0.62±0.07 mm2), showed less bone loss (p<0.05) than Group C (1.35±0.25 mm2; 1.40±0.31 mm2; 1.29±0.27 mm2), respectively. Conclusions: Subgingival irrigation with TTC-HCL was an effective adjunctive treatment for periodontal disease induced in rats.
Keywords: Irrigation; Periodontal diseases; Periodontitis; Rats; Tetracycline